NUMERICAL SIMULATION OF SUBSONIC AND TRANSONIC FLOW AROUND THIN SHELLS - A. A. Dyadkin; A. Yu. Lutsenko; D. K. Nazarova (Научный вестник МГТУ ГА, 2016)
Numerical simulation of flow around a nose fairing half of a launch vehicle was carried out, aerodynamic characteristics of the model were calculated at subsonic and transonic flow velocities, the flow patterns around a thin shell were analyzed.